"دور المشرف التربوي في تنمية الكفايات التعليمية اللغة العربية بمرحلة التعليم الثانوي بليبيا " دراسة ميدانية بمدينة طرابلس - Mousa AbdulRahman Bkda (Universiti Sains Islam Malaysia, 2024)
The study aims at recognizing the role of the education supervisors in developing the educational competencies for Arabic language teachers concerning lesson planning, varying the teaching methods, using the educational resources, managing classrooms, and evaluating techniques. it also aims at recognizing the differences in opinion among the study population regarding the role of the supervisor in developing the competencies of the Arabic language teachers with regard to the study variables (gender, qualification, experiences, courses taken and training programs). Finally, it aims at recognizing the difficulties that encounter the education supervisor while developing the educational competencies for the secondary school Arabic language teachers. The researcher used the Analytic Descriptive Approach in the comprehensive survey. the study population was (420) secondary school Arabic language teachers in the Libyan capital Tripoli. A questionnaire comprised these main aspect: lesson planning, varying teaching methods, using educational resources, managing classrooms, evaluating techniques and difficulties encountering the educational supervisor while developing the educational competencies. Some of the most important study results can be summarized as follows: the educational supervisors carry out their roles in developing the education competencies concerning lesson planning, varying teaching methods, using educational resources,managing classrooms and evaluating techniques. The educational supervisors face difficulties while carrying out their roles in developing the educational competencies for secondary school Arabic language teachers concerning the study aspects. The study recommends that in-service training is carried out regularly and yearly for updating teachers' knowledge in education in general and in Arabic language teaching in particular. And identify the difficulties faced by supervisors and work to find appropriate solutions.